2022
DOI: 10.18632/aging.204224
|View full text |Cite
|
Sign up to set email alerts
|

SAAL1, a novel oncogene, is associated with prognosis and immunotherapy in multiple types of cancer

Abstract: Serum amyloid A-like 1 (SAAL1) was recently identified as a novel oncogene in hepatocellular carcinoma (HCC).To explore the potential role of SAAL1 in other cancers, we conducted a pan-cancer analysis of SAAL1 expression and its association with tumor microenvironment (TME) immunological profiles, sensitivity to chemotherapy agents, response to immunotherapy, and patient prognosis. SAAL1 was overexpressed in most malignant tumors in association with poor prognosis. Moreover, its expression was positively corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In this research, we confirmed the role of SAAL1 in LAC progression by utilizing bioinformatics analysis and basic research. The findings of the present study reflect the results of Chu et al in HCC [ 8 , 22 ], indicating that SAAL1 could play an oncogenic role in LAC progression. However, this study has the following deficiencies: 1) we should further collect the tissue samples from LAC patients to detect SAAL1 expression levels, and explore the relationship between SAAL1 expression and clinical data of LAC patients to evaluate the clinical values of SAAL1; 2) we will add more LAC cell lines to verify the roles and mechanisms of SALL1 in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this research, we confirmed the role of SAAL1 in LAC progression by utilizing bioinformatics analysis and basic research. The findings of the present study reflect the results of Chu et al in HCC [ 8 , 22 ], indicating that SAAL1 could play an oncogenic role in LAC progression. However, this study has the following deficiencies: 1) we should further collect the tissue samples from LAC patients to detect SAAL1 expression levels, and explore the relationship between SAAL1 expression and clinical data of LAC patients to evaluate the clinical values of SAAL1; 2) we will add more LAC cell lines to verify the roles and mechanisms of SALL1 in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have discovered the overexpression of the inflammatory gene SAAL1 in HCC. Furthermore, elevated SAAL1 expression was had something to do with shorter OS in patients with HCC [ 8 , 22 ]. Therefore, inhibition of SAAL1 expression could inhibit the growth and migration ability of HCC cells, impair the AKT/mTOR phosphorylation cascade driven by HGF/MET, and increase the sensitivity of HCC cells to sorafenib and foretinib [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-TMB tumors tend to respond better to immunotherapy due to the creation of more neoantigens. Examples include melanoma, lung, bladder, and head and neck cancers, which also benefit from PD-1 or PD-L1 immune checkpoint inhibitors [14]. However, prostate, pancreatic, and glioblas-toma tumors have a low TMB and tend to be resistant to immunotherapy, suppressing the immune system through various mechanisms such as reduced immune checkpoint expression or immunosuppressive molecule expression [15,16].…”
Section: Current Status Of Cancer Immunotherapy and Cancer Personaliz...mentioning
confidence: 99%
“… 18 It has also been suggested that high SAA1expression levels in tumor tissues may be associated with resistance to common chemotherapy drugs including paclitaxel, platinum-based drugs, and 5-fluorodeoxyuridine. 19 Given the important role of systemic inflammation in regulating the development and progression of pancreatic cancer, and the influence of SAA1 expression in tumor tissue on the efficacy of chemotherapy, it is important to investigate the prognostic value of circulating SAA in patients with APC received chemotherapy.…”
Section: Introductionmentioning
confidence: 99%